Preparation method and application of nano-titanium dioxide loaded silica gel ball dehydration material

By preparing nanotitanium dioxide-loaded silica ball dehydration materials, the problem of low moisture removal efficiency in the prior art is solved, and a more efficient moisture removal effect is achieved, and the cost is low and the preparation is simple.

CN118925660BActive Publication Date: 2025-04-11WUHAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411177023.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-04-11
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The existing dehydration materials have low moisture removal efficiency in decommissioned transformer oil, and have problems such as large energy consumption and low efficiency.

Method used

The preparation method of nanotitanium dioxide-loaded silica ball dehydration material is adopted. By preparing an ethanol solution, adding tetrabutyl titanate and dilute hydrochloric acid for heating and stirring, then adding silica powder, and finally undergoing multiple stages of high-temperature heating and drying, a nanotitanium dioxide-loaded silica ball material was obtained.

Benefits of technology

The moisture removal efficiency is improved, and the oil sample meets the standard of 35μg/mL after treatment, which solves the problem of low efficiency of existing dehydrated materials, and is low in cost and is simple and efficient in preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118925660B_ABST
    Figure CN118925660B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of dehydration materials, and specifically to a preparation method and application of a nano-titanium dioxide-loaded silica gel ball dehydration material. An ethanol solution is added to tetrabutyl titanate and dilute hydrochloric acid, heated and stirred under water bath and magnetic stirring conditions, and then silica gel powder is added and stirred continuously to obtain a titanium dioxide-loaded silica gel ball sol; the titanium dioxide-loaded silica gel ball sol is poured into a porcelain boat and placed in a tube furnace for multi-stage high-temperature heating and then cooled and dried to obtain a nano-titanium dioxide-loaded silica gel ball material. The adsorption material prepared by the present invention uses common materials such as tetrabutyl titanate and column chromatography silica gel balls as raw materials for preparation, has low cost, and the preparation method is simple and efficient. It is an effective and renewable adsorption material for removing moisture from waste insulating oil. In addition, in the treatment of water-containing oil samples, the result data is good, and the oil sample after adsorption meets 35μg / mL, thereby solving the problem of low water removal efficiency of existing dehydration materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dehydration materials, and in particular to a preparation method and application of a nano titanium dioxide loaded silica gel ball dehydration material. Background Art

[0002] Moisture is one of the common contaminants in retired transformer oil. It will have a certain impact on the oil, mainly including the following aspects: reduce insulation performance. Moisture will cause the dielectric strength in the oil to decrease, thereby reducing the insulation performance of the oil. This will increase the risk of insulation breakdown of the equipment and affect the safe operation of the equipment; promote oil oxidation. The presence of moisture in transformer oil will promote the oxidation reaction of the oil and accelerate the aging of the oil. The oxidized oil will produce acidic substances, further aggravating the degradation of the oil and affecting the normal operation of the equipment; increase thermal conductivity. The presence of moisture will increase the thermal conductivity of the oil and cause the heat dissipation performance of the oil to decrease. This will cause the temperature of the equipment to rise during operation, affecting the stability and life of the equipment; affect the physical properties of the oil. Moisture will change the physical properties of the oil, such as viscosity, density, etc., affecting the fluidity and lubrication performance of the oil. Therefore, when there is moisture in the transformer oil, timely measures need to be taken to deal with it, such as removing moisture through oil-water separation equipment to ensure the quality and insulation performance of the oil and ensure the safe operation of the equipment.

[0003] The existing technologies for removing moisture from retired transformer oil often have problems such as high energy consumption and low efficiency. For example, the dehydration system using a hydrophobic membrane oil-water separation device can remove more water from the oil, but it is still not effective for trace water, and the system pressure drop is large, causing greater wear on the membrane structure. Traditional aluminum-based adsorbents are low in price and widely used, but have low purity and limited purification accuracy. Therefore, it is still necessary to develop new adsorbents to break through the retired oil dehydration technology. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a nano-titanium dioxide-loaded silica gel ball dehydration material, aiming to solve the problem of low water removal efficiency of existing dehydration materials.

[0005] To achieve the above object, in a first aspect, the present invention provides a method for preparing a nano-titanium dioxide-loaded silica gel ball dehydration material, comprising the following steps:

[0006] preparing an ethanol solution;

[0007] The ethanol solution is added to tetrabutyl titanate and dilute hydrochloric acid, heated and stirred in a water bath under magnetic stirring conditions, and then silica gel powder is added and stirred continuously to obtain a titanium dioxide-loaded silica gel sphere sol;

[0008] The titanium dioxide-loaded silica gel ball sol is poured into a porcelain boat and placed in a tube furnace for multi-stage high-temperature heating and then cooled and dried to obtain a nano-titanium dioxide-loaded silica gel ball material.

[0009] Wherein, in "preparing an ethanol solution", the ethanol solution is prepared by dissolving anhydrous ethanol in distilled water.

[0010] Among them, in "adding the ethanol solution to tetrabutyl titanate and dilute hydrochloric acid, heating and stirring in a water bath and magnetic stirring conditions, adding silica gel powder and continuing to stir to obtain titanium dioxide loaded silica gel sphere sol", the volume of tetrabutyl titanate is 0.5-8ml, the volume of the ethanol aqueous solution is 25-50mL, and the volume concentration of the ethanol aqueous solution is 50%-80%.

[0011] Among them, in "adding the ethanol solution to tetrabutyl titanate and dilute hydrochloric acid, heating and stirring in a water bath and magnetic stirring conditions, adding silica gel powder and continuing to stir to obtain titanium dioxide loaded silica gel sphere sol", the water bath temperature is 25°C-50°C, the magnetic stirring speed is 100r / min-300r / min, the stirring time is 5min-10min, and the mixing and stirring time after adding the silica gel powder is 5min-15min.

[0012] Among them, in "the titanium dioxide loaded silica gel ball sol is poured into a porcelain boat and placed in a tubular furnace for multi-stage high-temperature heating and then cooled and dried to obtain a nano titanium dioxide loaded silica gel ball material", the first stage of the multi-stage high-temperature heating is 80℃-120℃, 10min-40min; the second stage: 200℃-300℃, 10min-40min; the third stage: 450℃-550℃, 1.5h-2.5h; the heating rate is 5℃ / min-20℃ / min.

[0013] Among them, in “the titanium dioxide loaded silica gel ball sol is poured into a porcelain boat and placed in a tubular furnace for multiple stages of high-temperature heating and then cooled and dried to obtain a nano-titanium dioxide loaded silica gel ball material”, the nano-titanium dioxide loaded silica gel ball material is column chromatography silica gel, and its diameter is about 50 μm.

[0014] In the second aspect, an application of a nano-titanium dioxide-loaded silica gel ball dehydration material is provided, using the preparation method of the nano-titanium dioxide-loaded silica gel ball dehydration material described in the first aspect, characterized in that:

[0015] The nano titanium dioxide loaded silica gel ball material is applied to dehydration of transformer oil.

[0016] The preparation method of a nano-titanium dioxide-loaded silica gel ball dehydration material of the present invention comprises the following steps: preparing an ethanol solution; adding the ethanol solution to tetrabutyl titanate and dilute hydrochloric acid, heating and stirring under water bath and magnetic stirring conditions, adding silica gel powder and continuing stirring to obtain a titanium dioxide-loaded silica gel ball sol; pouring the titanium dioxide-loaded silica gel ball sol into a porcelain boat and placing it in a tube furnace for multi-stage high-temperature heating and then cooling and drying to obtain a nano-titanium dioxide-loaded silica gel ball material. The adsorption material prepared by the present invention uses common materials such as tetrabutyl titanate and column chromatography silica gel balls as raw materials for preparation, has low cost, and the preparation method is simple and efficient. It is an effective and renewable adsorption material for removing moisture from waste insulating oil. In addition, in the treatment of water-containing oil samples, the result data is good, and the oil sample after adsorption meets 35μg / mL, thereby solving the problem of low water removal efficiency of existing dehydration materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention is further illustrated by means of the non-limiting examples given in the accompanying drawings.

[0018] Figure 1 The present invention is a flow chart of a method for preparing a nano titanium dioxide loaded silica gel ball dehydration material.

[0019] Figure 2 This is a scanning electron microscope image of the material.

[0020] Figure 3 It is an element analysis diagram. DETAILED DESCRIPTION

[0021] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0022] See also Figures 1 to 3 In a first aspect, the present invention provides a method for preparing a nano-titanium dioxide-loaded silica gel ball dehydration material, comprising the following steps:

[0023] S1 prepares an ethanol solution;

[0024] The ethanol solution is prepared by dissolving anhydrous ethanol in distilled water.

[0025] Specifically, 25 mL of anhydrous ethanol was dissolved in 20 mL of distilled water to prepare 45 mL of ethanol solution.

[0026] S2: adding the ethanol solution to tetrabutyl titanate and dilute hydrochloric acid, heating and stirring in a water bath under magnetic stirring conditions, adding silica gel powder and continuing to stir to obtain a titanium dioxide-loaded silica gel sphere sol;

[0027] The volume of tetrabutyl titanate is 0.5-8 ml, the volume of ethanol aqueous solution is 25-50 ml, the volume concentration of ethanol aqueous solution is 50%-80%, the water bath temperature is 25°C-50°C, the magnetic stirring speed is 100 r / min-300 r / min, the stirring time is 5 min-10 min, and the mixing and stirring time after adding the silica gel powder is 5 min-15 min.

[0028] Specifically, 1 mL of tetrabutyl titanate and 1 mL of 1% dilute hydrochloric acid were added dropwise, and heated and stirred at 40°C and 200 r / min using a magnetic stirrer. After the solution became slightly viscous, 2 g of silica gel powder was added, and stirred for a while to prepare a nano-titanium dioxide-loaded silica gel sphere sol.

[0029] S3: pouring the titanium dioxide loaded silica gel ball sol into a porcelain boat and placing it in a tube furnace for multi-stage high-temperature heating and then cooling and drying to obtain a nano titanium dioxide loaded silica gel ball material.

[0030] The first stage of the multi-stage high temperature heating is 80℃-120℃, 10min-40min; the second stage: 200℃-300℃, 10min-40min; the third stage: 450℃-550℃, 1.5h-2.5h; the heating rate is 5℃ / min-20℃ / min. The nano-titanium dioxide loaded silica gel ball material is column chromatography silica gel, and its diameter is about 50μm.

[0031] Specifically, the sol was poured into a porcelain boat, placed in a tube furnace and heated at a heating rate of 10°C / min, kept at 105°C for 30 minutes, kept at 250°C for 20 minutes, and then kept at 500°C for 2 hours. After cooling, nano-titanium dioxide-loaded silica gel ball powder was obtained.

[0032] S1: Dissolve 25 mL of anhydrous ethanol in 20 mL of distilled water to prepare 45 mL of ethanol solution, add 1 mL of tetrabutyl titanate and 1 mL of 1% dilute hydrochloric acid dropwise, heat and stir with a magnetic stirrer at 40°C, 200 r / min, add 2 g of silica gel powder when the solution becomes slightly viscous, and stir for a while to prepare nano-titanium dioxide-loaded silica gel ball sol.

[0033] S2: Pour the sol into a porcelain boat and heat it in a tube furnace at a heating rate of 10°C / min, keep the temperature at 105°C for 30 minutes, 250°C for 20 minutes, and then keep the temperature at 500°C for 2 hours. After cooling, nano-titanium dioxide-loaded silica gel ball powder is obtained.

[0034] Example 2

[0035] This embodiment provides a method for preparing a nano-titanium dioxide-loaded silica gel ball dehydration material. The difference between this embodiment and embodiment 1 is only that:

[0036] In step S1, 4 ml of tetrabutyl titanate and 42 ml of ethanol aqueous solution were mixed;

[0037] Step S2 is the same as that of Example 1.

[0038] Example 3

[0039] This embodiment provides a method for preparing a nano-titanium dioxide-loaded silica gel ball dehydration material. The difference between this embodiment and embodiment 1 is only that:

[0040] In step S1, 8 ml of tetrabutyl titanate and 38 ml of anhydrous ethanol are mixed;

[0041] Step S2 is the same as that of Example 1.

[0042] The products of Example 1, Example 2 and Example 3 were used to treat oil samples with a water content of 100 μg / ml. The water contents after treatment were 30.68 μg / mL, 32.63 μg / mL and 34.87 μg / mL respectively.

[0043] The scanning electron microscope and mapping element analysis of the material prepared by this method are shown in Figures 2 and Figure 3 As shown;

[0044] Figure 2 Figure 1. SEM and EDS mapping of adsorbent: (a) image of silica gelsphere. (b) surface of silica gel sphere. (c) surface of nTiO2@SGS. (e) ~ (g) elemental distribution of O, Si and Ti. Figure 2 In the figure, a~c are material structure images of different scales; e~g are element distribution maps obtained by EDS mapping, which are O, Si, and Ti respectively.

[0045] Figure 3 Figure 2.Elemental analysis of nTiO2@silica gel sphere. Figure 3 This is an elemental composition analysis diagram for the material.

[0046] In the second aspect, an application of a nano-titanium dioxide-loaded silica gel ball dehydration material is provided, using the preparation method of the nano-titanium dioxide-loaded silica gel ball dehydration material described in the first aspect, characterized in that:

[0047] The nano titanium dioxide loaded silica gel ball material is applied to dehydration of transformer oil.

[0048] The beneficial effects of the technical solution of the present invention are as follows:

[0049] 1. The column chromatography silica gel ball used in the present invention has a diameter of about 50 μm, a porous structure, and stable physical and chemical properties. It is a good adsorption material in itself. It is used as a material base material in this invention, which further improves the stability and adsorption effect of the composite material. nTiO2 also has certain adsorption properties, but when used to remove water from oil, it often encounters agglomeration. Through the combination of the two, while ensuring the stability of the adsorption material, it overcomes the disadvantages of a single material, and works together to improve the dehydration effect and the value of the material;

[0050] Second, the adsorption material prepared by the present invention uses common materials such as tetrabutyl titanate and column chromatography silica gel balls as raw materials, which has low cost and a simple and efficient preparation method;

[0051] 3. The adsorption material prepared by the present invention has a lychee-like shape, which increases the adsorption sites of the material and improves the dehydration effect. According to the test, the water removal rate of the material in 200 μg / mL of aqueous insulating oil is 82.69%, and the water content of the oil sample after treatment is 34.62 μg / mL. The water content index of the insulating oil after adsorption meets the application standard;

[0052] What is disclosed above is only one or more preferred embodiments of the present application, and cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A method for preparing a nano-titanium dioxide-loaded silica gel ball dehydration material, characterized in that: The following steps are involved: preparing an ethanol solution; The ethanol solution is added to tetrabutyl titanate and dilute hydrochloric acid, heated and stirred in a water bath under magnetic stirring conditions, and then silica gel powder is added and stirred continuously to obtain a titanium dioxide-loaded silica gel sphere sol; The titanium dioxide-loaded silica gel ball sol is poured into a porcelain boat and placed in a tube furnace for multi-stage high-temperature heating and then cooled and dried to obtain a nano-titanium dioxide-loaded silica gel ball material.

2. The method for preparing the nano-titanium dioxide loaded silica gel ball dehydration material according to claim 1, characterized in that: The ethanol solution is prepared by dissolving anhydrous ethanol in distilled water.

3. The method for preparing the nano-titanium dioxide loaded silica gel ball dehydration material according to claim 1, characterized in that: The volume of tetrabutyl titanate is 0.5-8 ml, the volume of the ethanol solution is 25-50 mL, and the volume concentration of the ethanol solution is 50%-80%.

4. The method for preparing the nano-titanium dioxide loaded silica gel ball dehydration material according to claim 3, characterized in that: The water bath temperature is 25° C.-50° C., the magnetic stirring speed is 100 r / min-300 r / min, the stirring time is 5 min-10 min, and the mixing and stirring time after adding the silica gel powder is 5 min-15 min.

5. The method for preparing the nano-titanium dioxide loaded silica gel ball dehydration material according to claim 1, characterized in that: The first stage of the multi-stage high-temperature heating is 80°C-120°C, 10min-40min; the second stage: 200°C-300°C, 10min-40min; the third stage: 450°C-550°C, 1.5h-2.5h; the heating rate is 5°C / min-20°C / min.

6. The method for preparing the nano-titanium dioxide loaded silica gel ball dehydration material according to claim 5, characterized in that: The nano-titanium dioxide loaded silica gel ball material is column chromatography silica gel, and the diameter thereof is about 50 μm.

7. An application of a nano-titanium dioxide loaded silica gel ball dehydration material, characterized in that: The nano-titanium dioxide-loaded silica gel ball dehydration material obtained by the preparation method of the nano-titanium dioxide-loaded silica gel ball dehydration material according to any one of claims 1 to 6 is applied to the dehydration of transformer oil.